2009
DOI: 10.1177/0255761409102320
|View full text |Cite
|
Sign up to set email alerts
|

Peer learning and reflection: strategies developed by vocal students in a transforming tertiary setting

Abstract: The focus of this article is on the analysis of reflection and peer learning in the pedagogical environment. The research draws on findings from an Australian study, which aimed to develop and critically evaluate a model of vocal pedagogy influenced by socio-cultural theories. The model sought to position Vygotsky's theories in the environment of university-level vocal instruction. To capture the developmental nature of this pedagogical project, a design-based development research methodology was employed. Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…The peer education aspect of this delivery model draws on the work of Topping (2005Topping ( , 2009) with regard to the theory of learning and the review of Medley et al (2009) with regard to its successful implementation. In music education Latukefu (2009) has since published her successful use of this peer education approach to vocal training with higher education students.…”
Section: Methodsmentioning
confidence: 99%
“…The peer education aspect of this delivery model draws on the work of Topping (2005Topping ( , 2009) with regard to the theory of learning and the review of Medley et al (2009) with regard to its successful implementation. In music education Latukefu (2009) has since published her successful use of this peer education approach to vocal training with higher education students.…”
Section: Methodsmentioning
confidence: 99%
“…These studies did not involve music students, but the results have been substantiated for this student group as well. In a study on group teaching among tertiary voice students (Latukefu 2009(Latukefu , 2010, the students reported that taking part in peer assessment helped improve their own performance. In their discussion of the positive effects of peer assessment, Searby and Ewers (1997, 381) claim that students will develop a deeper and more critical understanding of musical performance and the processes involved when asked to assess fellow students; the learning goals will become clearer as they gain a better understanding of the assessment criteria.…”
Section: Issues To Be Discussedmentioning
confidence: 99%
“…Kooskõlas eelnevaga võimaldab refl eksioon pilliõppes tõhustada instrumendi harjutamist, sest refl ekteerimine aitab mõtestada oma nõrku külgi ning jõuda lahenduseni, kuidas neid parandada (Parncutt, 2007). Samuti aitab eneseregulatsioonimeetodite (sh refl eksiooni) kasutamine kaasa sellise iseseisva õppija kujunemisele, kes on suuteline oma õpiprotsessi juhtima (Zimmerman, 2002) ning võtma selle eest vastutuse (Latukefu, 2009). Dewey (1933) refl ekteeriva mõtlemise teoorias on tegevus ja mõtlemine omavahel põimunud ja toimuvad korraga.…”
Section: Refl Eksiooni Mõisteunclassified
“…Tulemustest nähtub, et refl eksioonimudeli rakendamisel pilliõppes on palju positiivseid mõju tegureid. Uuringus osalenud üliõpilaste hinnangul võimaldab video näha ennast objektiivsemast vaatenurgast, mis on oluline refl eksiooni eeltingimus (vt nt Leijen et al, 2009b;van den Berg, 2001), ning ülesannete täitmine distsiplineerib end süstemaatiliselt arendama (Latukefu, 2009), aitab keskenduda konkreetsetele eesmärkidele ning fookustada harjutamist. Kooskõlas Parncutti (2007) tähelepanekutega võib uuringu tulemuste põhjal väita, et üliõpilased tajusid refl eksioonimudeli positiivset mõju pilliharjuta misele: nad õppisid ära tundma ja mõtestama oma nõrku külgi ning jõudma lahendusteni, kuidas neid parandada, mis on kooskõlas pragmatistliku refl eksiooni käsitluse eesmärkidega.…”
Section: Refl Eksiooniülesannete Kasutegurid Pilliõppesunclassified
See 1 more Smart Citation